Histopathological study of ovarian neoplasms in a tertiary healthcare center of Madesh Province - Fahad Alam; Anand Kumar Chaurasiya; Md. Kalim Akhtar; Brijesh Shrestha (Journal of Pathology of Nepal)
Background: Ovarian tumors are a common form of neoplasm in women. Early diagnosis and management of ovarian tumors is a major problem in a developing country like Nepal, due to lack of awareness and limited facility for investigations in all parts of Nepal. Usually, the malignant ovarian neoplasms will have already advanced too far by the time they are detected. This study was proposed to identify the spectrum of ovarian tumors and their clinicopathological features.